Negosiasi Halal di Inggris yang Sekuler: Regulasi, Politik Budaya, dan Adaptasi Pasardalam Konteks Minoritas Muslim - Dini Astriani (Prodi Ekonomi Syariah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2026)
This article explores halal practices in the United Kingdom as a hybrid phenomenon emerging from the complex interaction between secular state regulation, the fragmentation of Islamic religious authority, and capitalist market logics. Employing a qualitative interpretive approach, the study draws on academic literature, regulatory documents, and empirical reflections on halal markets and consumption practices in Britain. Departing from conventional understandings that prioritize normative compliance or Muslim consumption alone, this research demonstrates that halal is produced and negotiated through legal frameworks, certification regimes, industrial strategies, and the everyday practices of minority Muslim communities. The British state functions as a technical regulator without recognizing any specific Islamic religious authority, thereby creating both adaptive space and epistemic uncertainty for Muslim consumers. Market actors respond by mobilizing neutral-secular discourses (such as quality, food safety, and universal ethics), enabling halal products to be accepted by both Muslim and non-Muslim consumers while simultaneously reproducing public secularism. Halal consumption among minority Muslims unfolds in pragmatic and situational ways, negotiating between religious obligations and structural constraints. These findings lead to the conceptualization of hybrid halal: a form of practice situated in the “in-between space” of religious norms, secular regulation, and market rationality. Theoretically, this study enriches scholarship on Islam in Europe by highlighting minority religious adaptation through banal and procedural practices. Empirically, it demonstrates how interactions among the state, the market, and Muslim communities shape the meaning and legitimacy of halal in a predominantly non-Muslim society.